Phenotypic characterization of wheat landraces from mid and far western districts of Nepal - Dangi, Sangharash Raj; Puri, Ramesh Raj; Gautam, Nutan Raj (International Journal of Environment, 2015)
The study was conducted to evaluate phenotypic variation in one hundred and sixty six wheat landraces from mid and far western districts of Nepal. They were sown in randomized complete block design with two replications at National Wheat Research Program in 2014/15. The observed traits were analyzed using descriptive statistics and multivariate analysis using MINITAB v. 14. The results showed a wide range of phenotypic variability in observed parameters. The results also showed that the highest value of the standard deviation from mean (Sd) was for grain yield (±290.10) followed by plant height (±7.21). Among the traits the lowest deviation from mean (Sd) was for thousand grain weight TGW (±2.68). Wheat landraces grouped in four clusters depending on similarity of the studied traits. The results in this cluster, showed that days to maturity ranged from 97 to111 days, TGW ranged from 16 to17 gm, plant height ranged from 76 to 85 cm, and grain yield ranged from 2800 to 3000 Kg ha-1. Wheat landraces under study are grouped depending on specific traits useful for wheat improvement program. Results of this study can be supportive to detect wheat landraces within species with similar traits. In addition it can be useful for sampling in successive studies and parental selection in wheat breeding program.International Journal of Environment Vol.4(4) 2015: 32-44